Microsoft dynamics AX 2012 R2 services : harness the power of Microsoft Dynamics AX 2012 R2 to create and use your own services effectively /: harness the power of Microsoft Dynamics AX 2012 R2 to create and use your own services effectively. (2014) - Unknown
No abstract available